Psychological monitoring and modulation of training load of world-class canoeists - Berglund, B.; Safstrom, H. (Medicine & Science in Sports & Exercise, 1994)
POMS to indicate the onset of overtraining. Athletes are at risk of developing staleness (overtraining) when (a) global POMS scores are more than 50% over the individual basal off-season global POMS as well as, (b) the measure of fatigue is greater than the measure of vigor. This is a RISK LEVEL and is used to indicate when to lower the training load. Rating of training load (RTL). A rating scale that has been used to assess a week's training stress is the RTL. It is as follows: 2 = very, very easy 4 = very easy 6 = easy 8 = average 10 = hard 12 = very hard 14 = very, very hard Rating of training speed (RTS). A scale for measuring training speed is as follows: 1 = low intensity "jogging" 2 = mean speed for long distance racing (>60 min) 3 = threshold speed (mean speed in a 30-min race) 4 = mean speed during a 4-min race 5 = maximum speed during a 30-s race